유회수기 구조와 외부 진동에 따른 기름 박리 과정의 제거 성능에 대한 수치 연구 - 이채원(C. Lee); 최근혁(G. Choi); 김성진(S.J. Kim); 신승원(S. Shin) (한국전산유체공학회지, 2024)
With growing interests in the marine environment, endeavors aimed at reducing impact from pollutants are being increased. Fuel with lower sulfur acid becomes popular since it can reduce pollutants with relatively low cost. However, this Low Sulfur Fuel Oil exhibits large viscosity at lower temperature as it tends to adhere strongly to oil recovery devices impeding the effectiveness of continuous oil removal. Recently, it has been proposed that hydrophilic surface treatment can increase the peeling performance of oil from surface. Our previous work was focused on identifying peeling mechanism acting on vertically dipping plate through numerical investigation. In this study, we are aiming to get insights for increased peeling performance from rachet structure since it can minimize contact between oil and the solid structure. At the same time, we also want to find out environmental effect from wave induced vibration in oceanic environment. The effect from wave amplitude, frequency, and direction will be studied in detail for both flat and ratchet geometries. It has been found that hydrophilic ratchet geometry is very effective for oil removal and the removal performance is enhanced by wave induced vibration contrary to the flat surface. KCI Citation Count: 0